THE IMPLEMENTATION OF FLIPPED LEARNING IN LIA - Azhari, Andry; Yuniko, Fajrilhuda (LINGUA LITERA : journal of english linguistics and literature, 2024)
This research aimed to find out and explain in detail how LIA teachers in West Sumatera apply flipped learning since this institution has successfully applied this learning process since 2018 (even before the Pandemic). This study also found problems faced by LIA teachers in conducting flipped learning and ways to solved the problems. An ethnographic research was conducted to study how teachers in LIA applied flipped learning since it is considered as an in-depth study of a particular group of people in their own environment. The researchers observed their routines activities, participated in their activities, and conducted in-depth interviews. Moreover, the researchers studied not only observed the teachers but also all component that supported the implementation of flipped learning in LIA. There were 3 LIA branches and there were 7 teachers observed (3 teachers are in LIA Padang, 2 teachers are in LIA Bukittinggi, and the others are from LIA Payakumbuh). From the research, it was found that Flipped learning in LIA is compulsory. All teachers need to follow the guidance and procedures that has been instructed by the TTD (Teachers Training Development). However, different teachers have different techniques in fulfilling every step of the procedures. This research explains the guidance and steps of how flipped materials implemented in LIA. It can be a great source for other teachers to find out how to apply it in their own class.